Identification of heteromolecular binding sites in transcription factors Sp1 and TAF4 using high‐resolution nuclear magnetic resonance spectroscopy. (27th September 2017) - Hibino, Emi; Inoue, Rintaro; Sugiyama, Masaaki; Kuwahara, Jun; Matsuzaki, Katsumi; Hoshino, Masaru
Abstract: The expression of eukaryotic genes is precisely controlled by interactions between general transcriptional factors and promoter‐specific transcriptional activators. The fourth element of TATA‐box binding protein‐associated factor (TAF4), an essential subunit of the general transcription factor TFIID, serves as a coactivator for various promoter‐specific transcriptional regulators. Interactions between TAF4 and site‐specific transcriptional activators, such as Sp1, are important for regulating the expression levels of genes of interest. However, only limited information is available on the molecular mechanisms underlying the interactions between these transcriptional regulatory proteins. We herein analyzed the interaction between the transcriptional factors Sp1 and TAF4 using high‐resolution solution nuclear magnetic resonance spectroscopy. We found that four glutamine‐rich (Q‐rich) regions in TAF4 were largely disordered under nearly physiological conditions. Among them, the first Q‐rich region in TAF4 was essential for the interaction with another Q‐rich region in the Sp1 molecule, most of which was largely disordered. The residues responsible for this interaction were specific and highly localized in a defined region within a range of 20–30 residues. Nevertheless, a detailed analysis of 13 C‐chemical shift values suggested that no significant conformational change occurred upon binding. These results indicate a prominent and exceptional binding mode for intrinsically disordered proteins other than the well‐accepted concept of "coupled folding and binding."